Cost Analysis of Inpatient Heart Failure Treatment at PKU Muhammadiyah Hospital of Yogyakarta Based on INA-CBG’s Tariffs in 2023 - Ingenida Hadning; Lidya Prames Wari; Nina Dwi Lestari (Sanata Dharma University, 2025)
The prevalence of heart failure in Indonesia has reached 1.5% of the entire population. Catastrophic heart failure requires long treatment, thus necessitating large costs. The Indonesian government regulates payments to advanced health facilities through INA-CBG tariffs. This study evaluated the INA-CBG tariffs based on the Ministry of Health Regulation No. 3 of 2023 for the treatment of inpatient heart failure. This study aims to determine the difference in the average actual costs of heart failure patients compared to the INA-CBG tariffs based on the Ministry of Health Regulation No. 3 of 2023. This research was conducted as an observational study with a cross-sectional design at PKU Muhammadiyah Hospital of Yogyakarta. Data on heart failure inpatients were gathered using a retrospective method from January to September 2023. Data were analyzed using descriptive analysis and a one sample t-test. The analysis found some average actual costs were higher than INA-CBG tariffs, with an insignificant difference. Real costs that the Social Security Agency (BPJS) on Health could not cover caused the hospital to suffer losses.The prevalence of heart failure in Indonesia has reached 1.5% of the entire population. Catastrophic heart failure requires long treatment, thus necessitating large costs. The Indonesian government regulates payments to advanced health facilities through INA-CBG tariffs. This study evaluated the INA-CBG tariffs based on the Ministry of Health Regulation No. 3 of 2023 for the treatment of inpatient heart failure. This study aims to determine the difference in the average actual costs of heart failure patients compared to the INA-CBG tariffs based on the Ministry of Health Regulation No. 3 of 2023. This research was conducted as an observational study with a cross-sectional design at PKU Muhammadiyah Hospital of Yogyakarta. Data on heart failure inpatients were gathered using a retrospective method from January to September 2023. Data were analyzed using descriptive analysis and a one sample t-test. The analysis found some average actual costs were higher than INA-CBG tariffs, with an insignificant difference. Real costs that the Social Security Agency (BPJS) on Health could not cover caused the hospital to suffer losses.